Health status and functional profile at admission of nursing home residents in Iceland over 11-year period. - Hjaltadottir, Ingibjörg; Rahm Hallberg, Ingalill; Kristensson Ekwall, Anna; Nyberg, Per (International Journal of Older People Nursing, 2011)
Health status and functional profile at admission of nursing home residents in Iceland over 11-year period. International Journal of Older People Nursing doi:10.1111/j.1748-3743.2011.00287.x Background. The knowledge over time of the health status and changes in care needs of newly admitted nursing home residents is limited. Objectives. To investigate trends in residents' health status and functional profile at admission to nursing homes and compare rural and capital areas in Iceland over an 11-year period. Design. Retrospective analysis of nursing home data over 11 years (1996-2006). Participants. Residents, who had been assessed with the Minimum Data Set assessment within 90 days from admittance (n = 2206). Method. Non-parametric tests for descriptive statistics and linear regressions were used to analyse time trends. Results. The mean age ranged from 80.1 to 82.8, and women accounted for 52.7% to 67.1%. The level of independency indicated intact cognitive performance in 28.6-61.4% and in 42.5-68% in activities of daily living performance. A weak, but significant, linear trend was seen in residents' health becoming less stable, their cognitive performance improving, more pain being reported and greater participation in social activities over the 11 years. Conclusion. Some residents might have stayed at home longer had they been given appropriate home care and the opportunity of rehabilitation. Pain management and social activities are areas where more staff knowledge seems to be needed. Implications for practice. Resources to enable old people to remain at home need to be explored before their entry into nursing homes. Whereas providing services at the appropriate level is important for society as well as older people.